2003
DOI: 10.1200/jco.2003.03.139
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Alone or With Dexamethasone for Previously Untreated Multiple Myeloma

Abstract: Thalidomide alone was effective in patients with newly diagnosed myeloma. The combination with dexamethasone induced a high frequency of response, rapid onset of remission, and low incidence of serious irreversible toxicity. These observations support further studies of this promising combination for patients with newly diagnosed multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
326
0
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(352 citation statements)
references
References 16 publications
17
326
0
9
Order By: Relevance
“…In line with these experimental data, Weber et al (1999) had reported that thalidomide restored the sensitivity of myeloma cells to dexamethasone-induced apoptosis. Recently, this observation was confirmed in larger cohorts by Dimopoulos et al (2001a) and Palumbo et al (2001), who reported partial responses in 41% and 55%.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In line with these experimental data, Weber et al (1999) had reported that thalidomide restored the sensitivity of myeloma cells to dexamethasone-induced apoptosis. Recently, this observation was confirmed in larger cohorts by Dimopoulos et al (2001a) and Palumbo et al (2001), who reported partial responses in 41% and 55%.…”
mentioning
confidence: 57%
“…Thalidomide has been attributed with additive or even synergistic activity when combined with pulsed dexamethasone, resulting in a doubling of the response rate in myeloma patients with post-transplantation relapse and low tumour burden (Weber et al, 1999;Barlogie et al, 2000). The first experience of thalidomide in combination with dexamethasone and cytotoxic chemotherapy was reported by Barlogie et al (2000), using the T-DCEP (thalidomide, dexamethasone, cyclophosphamide, etoposide, cisplatinum) and the DT-PACE (dexamethasone, thalidomide, cisplatinum, adriamycin, cyclophosphamide, etoposide) regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A higher response rate (64%) was observed only in newly diagnosed or untreated patients (Rajkumar et al, 2002). Weber et al (1999) achieved a response for THAL þ Dex in 35% of patients previously resistant to THAL or Dex alone. In our study, the combined treatment of THAL þ Dex had an increased response rate of 59.3% compared to THAL alone (55.1%).…”
Section: Discussionmentioning
confidence: 93%
“…Monotherapy thalidomide trials in advanced relapsed/refractory Richardson et al, 2004) as well as previously untreated asymptomatic MM Weber et al, 2003) (also known as 'smouldering' or indolent myeloma) have consistently shown partial response rates (SWOG criteria) of approximately 30%, with an acceptable safety profile. Thalidomide combined with dexamethasone in relapsed, refractory MM induces a partial response in 56% of patients (Palumbo et al, 2004a).…”
Section: Multiple Myelomamentioning
confidence: 99%